Effect of the size of nucleic acid delivery systems on their fate in cancer treatment - Mengyun Ye; Junni Gong; Wang Chen; Xiaoxuan Liu; Dandan Zhu (Exploration of Drug Science)
Nucleic acid therapeutics are emerging as a promising class of medicines, offering unique therapeutic options for cancer at the gene level. However, the druggability of nucleic acid therapeutics is fundamentally restricted by their low stability, poor membrane permeability, and low bioavailability, necessitating the use of delivery vectors. Various delivery vectors have been developed for nucleic acid therapeutics. The fate of established nucleic acid delivery systems (NADS) in vivo substantially affects the delivery efficiency and therapeutic efficacy. The physicochemical properties of NADS (such as size, charge, shape, etc) are crucial for the interaction of NADS with various biological barriers in the body, thereby determining the fate of NADS in the body. Nanoparticle (NP) size is an important parameter defining the blood circulation, distribution, tumor accumulation, and cellular uptake of NADS. This mini-review briefly introduces the various biological barriers of NADS in cancer treatment and focuses on the influence of the particle size of delivery vectors on the in vivo fate of NADS and their therapeutic efficacy, which provides new insights into the rational design of NADS.